INFLUENCE OF PERCEIVED ORGANIZATIONAL CULTURE AND EMOTION REGULATION ON WORK VIGOUR AMONG EMPLOYEES OF COMMERCIAL BANKS IN MAKURDI, BENUE STATE - Anshir, Stephen Simon; Tingir, Irene Torkwase; Ayorinde, Oluwafemi Ebenezer; Wombo, Samuel; Azizi, Stephen Aklome (African Journal of Social and Behavioural Sciences, 2024)
Following the continuous need for innovation prompted by increasing competition in the banking industry, banking organizations are saddled with the challenge of building and developing work vigour among their employees. Consequently, organizational researchers and professionals in the sector have started dedicating attention and resources to understanding the antecedents of employees’ work vigour. This study is therefore one of those research efforts targeted at understanding the antecedents of work vigour in the workplace by investigating Perceived Organizational Culture, Emotion Regulation and Work Vigour among employees of commercial banks in Makurdi, Benue State. Cross-sectional research approach was used and a total of 207 (147 males and 60 females) respondents were purposively selected for the study. Their ages ranged from 27-58 years with a mean age of 46.39 years. Fifty-seven of the participants were senior staff members while one hundred and fifty were junior staff members. Organizational Culture Scale (OCS), Emotion Regulation Scale (ERS) and Utrecht Work Engagement Scale (UWES) were used to assess Perceived organizational culture, Emotion regulation and work vigour of participants respectively. Results showed a significant positive prediction of perceived organizational culture on work vigour [F (1,201) =20.228, P<.001]. The results of the study also indicated that emotional regulation significantly predicted work vigour [F (1,201) =17.441, P<.001]. There was also a significant joint prediction of perceived organizational culture and emotion regulation on work vigour, [R2= .108, F (4, 202) =5.15, P< .001]. The implications of these findings to the banking sector were that favourable organizational culture will provide employees with better emotion regulation and the opportunity to exert more efforts towards achieving organizational goal. It was recommended among other things that bank employees should be provided with an enabling organizational culture where they could effectively control their negative emotions as this will make them demonstrate their unique skills thereby fostering work vigour.